2015
DOI: 10.1590/0034-7167.2015680416i
|View full text |Cite
|
Sign up to set email alerts
|

Custo direto da condução e documentação do processo de enfermagem

Abstract: the study promotes visibility of the work performed by nursing professionals in the development of the nursing process, providing financial data to ensure consistent arguments for proper resources to its feasibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…Research carried out to raise the ADC of activities performed by nursing professionals regarding the documentation of the Nursing Process, in a Medical Clinic Unit of a university hospital, resulted in an average time spent by nurses of 39.40 (SD = 14.61) minutes in activities related to admission (interview, physical examination, printing of reports), and 19.13 (SD = 8.36) minutes for activities related to the follow-up of hospitalized patients (organization of the documentation of the Nursing History and notes taken) ( 19 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research carried out to raise the ADC of activities performed by nursing professionals regarding the documentation of the Nursing Process, in a Medical Clinic Unit of a university hospital, resulted in an average time spent by nurses of 39.40 (SD = 14.61) minutes in activities related to admission (interview, physical examination, printing of reports), and 19.13 (SD = 8.36) minutes for activities related to the follow-up of hospitalized patients (organization of the documentation of the Nursing History and notes taken) ( 19 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Brazilian studies ( 19 , 20 , 21 , 22 , 23 ) which sought to identify the ADC of procedures performed by nursing professionals in care units, such as the intensive care unit (severely burned patients and patients with acute kidney injury), material and sterilization center (reprocessing of surgical drapes), and medical and surgical clinic (patients with incidence for the development of pressure injuries), observed that the duration of procedures performed by nurses, technicians and nursing assistants were similar in terms of variability, due to the complexity of the procedures and the professional’s knowledge and dexterity.…”
Section: Discussionmentioning
confidence: 99%
“…Outro fator que os pacientes relataram como importante foi o protagonismo no controle da dor, ou seja, só recebiam analgésicos quando consideravam que era necessário, bem como opiáceos somente se algia intensa 23 . compreensível levando-se em conta que é a partir do histórico de enfermagem que são realizadas as demais etapas da assistência de enfermagem como a identificação dos diagnósticos e a realização da prescrição do paciente 35 .…”
Section: Pesquisa Realizada Por Mcevoy Et Al Utilizando Como Base O P...unclassified
“…Isto posto, compreende-se a necessidade da implementação da segurança do paciente (SP) nos serviços de HD que envolva a equipe multiprofissional, mediante a realização de ações corretas e essenciais ao cuidado, como o uso de técnicas assépticas, prevenção de infecções e avaliações de parâmetros individuais. (11,12) Tais práticas fomentam uma assistência segura e qualificada exercida com protagonismo pela enfermagem, a qual possui papel primordial ao atuar também na resolução de intercorrências e monitoramento da HD, além de ser responsável pela execução da técnica, preparo do paciente, instalação do equipamento de diálise, somado à orientação sobre o procedimento e educação em saúde, práticas essas que demandam capacitação, treinamento e ferramentas que potencializem uma HD adequada e segura. (7,12,13) Nesse sentido, considera-se importante a construção de instrumentos que visem à promoção da SP no escopo de identificar o nível de segurança nos processos relacionados à assistência prestada no agreement greater than 80% and Content Validity Coefficient greater than 0.88, since the checklist showed a higher Content Validity Coefficient with 0.91.…”
Section: Introductionunclassified